Shifting the athlete's centre of gravity when performing a roundhouse kick (Mawashi-geri) - Matveev, D.A.; Levitskiy, A.G.; Potsipun, A.A.; Oshina, O.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyse changes in the coordinates of the athlete's overall centre of gravity during the demonstration of a Mawashi-geri roundhouse kick, performed both technically correctly and incorrectly. Methods and structure of the study. The experiment was conducted at the Petrodvorets District Olympic Reserve Sports School. During the study, video recordings were made of the athlete performing a Mawashi-geri kick with his right and left legs – a) technically correct and b) without turning the foot of the supporting leg. Each kick was performed three times. Results and conclusions. To describe the movement, the coordinate value ranges (quasi-attractors) of the overall centre of gravity and the centres of gravity of the athlete's body segments are used. In the case of a Mawashi-geri kick performed without turning the supporting leg, the values of the quasi-attractors of the striking leg are smaller compared to a kick performed with the supporting leg turned. The value of the quasi-attractor of the coordinates of the centre of gravity of the striking leg can be used as a criterion for identifying technical errors. The results of the study can be used to correct striking techniques in combat sports.